Role of type-2 innate lymphoid cells (ILC2s) in type-2 asthma. Issue 1 (February 2022) - Verma, Mukesh; Verma, Divya; Alam, Rafeul
Abstract : Purpose of review: The purpose of this review is to provide a synthesis of recent discoveries about type-2 innate lymphoid cells, especially, as they relate to the pathogenesis of asthma. Recent findings: We focused on features and characteristics of type-2 innate lymphoid cells (ILC2s) that distinguish them from other type-2 cells, especially Th2 cells. We collected and reviewed data related to human asthma and airway ILC2s. We examined the concept of ILC2 memory and trained immunity. We also analyzed steroid resistance of ILC2s, which is relevant for steroid-resistant asthma. Summary: The implications of the findings include an understanding of ILC2 inflammation, and pathways and molecules that can be targeted by biologics and other therapeutic agents for management severe and steroid-resistant asthma